Transformasi Akuntansi Digital dan Inovasi Bisnis UMKM di Era Digital: Pendekatan Netnografi - Sharon, St Salmah; Basir , Mustika Kusuma; Farmillah, Annisa Nadya; Pagiling, Novieanty; Burhanuddin, Fia Fauzia; Arif, Muh (Modus, 2026)
This study aims to explore the role of digital accounting transformation in supporting business innovation, particularly for micro, small, and medium enterprises (MSMEs) active on digital platforms, and to understand its contribution in increasing MSME adaptability in the digital economy era. This study uses a netnographic approach through three months of participatory observation in digital discussion forums, social media groups, and online communities that serve as interaction spaces for digital MSME actors. The unit of analysis is uploaded content, comments, and interactive discourses discussing digital accounting practices, the use of accounting software, and data-driven decision-making experiences in online spaces. The research findings indicate that digital accounting transformation not only improves the efficiency and accuracy of financial reporting, but also strengthens data-driven decision-making, encourages cross-platform collaboration, and enables faster responses to market dynamics through the integration of technologies such as artificial intelligence and automation in MSME business processes. However, this study has limitations because it focuses on observations in the digital space, so it does not fully represent the implementation of digital accounting in offline operational activities, and the involvement of business actors is still limited to online interactions. The implications of this study emphasize the importance of strengthening digital literacy capacity and developing adaptive accounting systems to support the sustainability of MSME business innovation in the digital economy era. The research's originality lies in the use of netnography method to examine the dynamics of digital accounting transformation within online MSME communities, an approach that is still relatively rare in contextual accounting research in the digital era. Keywords:    digital accounting; business innovation; digital economy; netnography; technological transformation.   Penelitian ini bertujuan untuk mengeksplorasi peran transformasi akuntansi digital dalam menopang inovasi bisnis, khususnya pada usaha mikro kecil dan menengah (UMKM) yang aktif di platform digital, serta memahami kontribusinya dalam meningkatkan daya adaptasi UMKM di era ekonomi digital. Penelitian ini menggunakan pendekatan netnografi melalui observasi partisipatif selama tiga bulan pada forum diskusi digital, grup media sosial, dan komunitas daring yang menjadi ruang interaksi pelaku UMKM digital dengan unit analisis berupa konten unggahan, komentar, dan diskursus interaktif yang membahas praktik akuntansi digital, penggunaan perangkat lunak akuntansi, serta pengalaman pengambilan keputusan berbasis data di ruang daring. Temuan penelitian menunjukkan bahwa transformasi akuntansi digital tidak hanya meningkatkan efisiensi dan ketepatan pelaporan keuangan, tetapi juga memperkuat pengambilan keputusan berbasis data, mendorong kolaborasi lintas platform, serta memungkinkan respons yang lebih cepat terhadap dinamika pasar melalui integrasi teknologi seperti kecerdasan buatan dan otomatisasi dalam proses bisnis UMKM. Namun demikian, penelitian ini memiliki keterbatasan karena berfokus pada observasi di ruang digital sehingga belum sepenuhnya merepresentasikan implementasi akuntansi digital pada aktivitas operasional offline, serta keterlibatan pelaku usaha yang masih terbatas pada interaksi daring. Implikasi penelitian ini menekankan pentingnya penguatan kapasitas literasi digital dan pengembangan sistem akuntansi yang adaptif guna mendukung keberlanjutan inovasi bisnis UMKM di era ekonomi digital. Orisinalitas penelitian terletak pada penggunaan metode netnografi untuk mengkaji dinamika transformasi akuntansi digital dalam komunitas daring UMKM, suatu pendekatan yang masih relatif jarang diterapkan dalam penelitian akuntansi kontekstual di era digital. Kata kunci:   akuntansi digital; inovasi bisnis; ekonomi digital; netnografi; transformasi teknologi.